Grape breeding is a key link in the development of the grapes and wine-making industry - E. A. Egorov (Вавиловский журнал генетики и селекции)
The article considers the legislative and regulatory acts that specify the tasks in the implementation of breeding processes. The results of the creation, variety testing, patenting and introduction of grape varieties and clones into the State Register of the Russian Federation for 2010–2020 are presented. The article analyzes the relationship between the indicators of industrial development with the production volumes of planting material, the use of domestic varieties that are included in the State Register of the Russian Federation. The characteristic of ampelographic collections – the genetic resources of grapes – is given. A comparative analysis of many years’ worth of data on the assessment of the adaptive potential of domestic varieties and introduced varieties is presented. The article describes domestic varieties, from which premium wines are produced, which not only competes with European varieties, but also surpasses the organoleptic properties and biochemical parameters of grape must and wine material. The main problems hindering the wide demand for domestic varieties on the market, including a substantial amount of imported European varietal planting material, are described. The necessity of accelerating breeding processes is actualized, modern methods are identified, including those of generative and genomic selection, transgenic technologies, cellular, mutational, and clone selection, and priority areas in breeding are presented. The numerical and qualitative analyses of the composition of breeding scientists is given, the trends of increasing the number and qualitative composition of breeders, the influx of young people, the growing need for training qualified personnel are noted. The number of bachelor’s, master’s and post-graduate students specializing in viticulture in general and in selection in particular as well as the number of defended dissertation studies on grape breeding has been found to be insufficient. The main scientific and practical problems in the organization and implementation of breeding processes in ensuring the development of the industry are updated, including a low share of domestic varieties in the produced planting material and planting, the lack of a systemically implemented varietal and technological policy, the imperfection of the legal system for the protection of intellectual property, a low availability of instrumentation and analytical equipment for the implementation of breeding by modern methods.